ANALISIS PENYEBAB TERJADI EROR DALAM TEGANGAN BATERAI 110 V PADA GARDU INDUK SEPATAN: Indonesia - Ratu Farah Humainah; Suhendar; Yuniar Rizky (Pusat Penelitian dan Pengabdian Masyarakat, 2023)
Functional power transmission system to reduce voltage from 150 kV to 20 kV as part of the main substation. During operation, the substation requires a DC power source as a control tool to support the performance of the substation. The source of direct current (DC) to the substation is taken from the rectifier and batteries installed in the installation parallel to the load or what is usually called a DC system. The battery is a backup DC source used to provide DC power to protection devices, PMT and PMS drive motors, as well as telecommunications equipment. To maintain battery reliability it is important to provide DC power in the event of a failure. Regular maintenance so that the battery can operate at peak performance. Battery maintenance is carried out by measuring voltage and weight, checking battery type, temperature and electrolyte capacity. This research was conducted to determine the reliability and suitability of 110V batteries at the Sepatan substation after maintenance. Results from testing the voltage per 110 Vdc battery cell at the Sepatan Main Substation with the SAFT NIFE brand, type SBLE 300-2, capacity 300 Ah, and a total of 88 cells. In the results of testing the voltage per 110 Vdc battery cell, the average battery voltage condition before BCT was 1.32 V, charging was carried out using the battery boosting method between 1.30 and 1.45 V, with this the average temperature of the battery 110 Vdc is 29oC and the specific gravity of the electrolyte in measuring this 110 Vdc battery is 1.221gr/cm3. In the 110 Vdc battery cell voltage test carried out for 5 hours with complete data, the total voltage measured was 112.7 V. In general, based on the capacity test results It could be said that the condition of the 110V batteries at the Sepatan 150 kV substation is always good and reliable or ready to be used when there is a problem.